2012
DOI: 10.1007/s10803-012-1547-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Responsiveness and Competence in Prader-Willi Syndrome: Direct Comparison to Autism Spectrum Disorder

Abstract: Prader-Willi syndrome (PWS), a neurodevelopmental disorder primarily characterized by hyperphagia and food preoccupations, is caused by the absence of expression of the paternally active genes in the proximal arm of chromosome 15. Although maladaptive behavior and the cognitive profile in PWS have been well characterized, social functioning has only more recently been systematically examined. Findings to date indicate the social impairment exhibited may reflect specific difficulty interpreting and using social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 46 publications
4
62
0
Order By: Relevance
“…Children aged 14 years had a developmental age of around 6 years in communication and socialization, indicating that the adaptive functioning of prepubertal children with PWS is less than half of healthy children. Social functioning in children with PWS has been described in earlier studies, and was also found to be significantly impaired compared to healthy peers (Dimitropoulos, Ho, & Feldman, 2012;Lo et al, 2013;Skokauskas, Sweeny, Meehan, & Gallagher, 2012). Additionally, social disabilities in PWS are more impaired than in other children with ID, indicating that the impaired social functioning is specific for PWS (Koenig, Klin, & Schultz, 2004;Wulffaert, Scholte, & Van Berckelaer-Onnes, 2010).…”
Section: Results In Relation To Previous Researchmentioning
confidence: 62%
“…Children aged 14 years had a developmental age of around 6 years in communication and socialization, indicating that the adaptive functioning of prepubertal children with PWS is less than half of healthy children. Social functioning in children with PWS has been described in earlier studies, and was also found to be significantly impaired compared to healthy peers (Dimitropoulos, Ho, & Feldman, 2012;Lo et al, 2013;Skokauskas, Sweeny, Meehan, & Gallagher, 2012). Additionally, social disabilities in PWS are more impaired than in other children with ID, indicating that the impaired social functioning is specific for PWS (Koenig, Klin, & Schultz, 2004;Wulffaert, Scholte, & Van Berckelaer-Onnes, 2010).…”
Section: Results In Relation To Previous Researchmentioning
confidence: 62%
“…Parents and caregivers of people with PWS are routinely faced with two types of problems; the control of access to food to avoid and/or minimize other health problems (such as obesity, scoliosis, and cardiovascular and endocrine illnesses) 12 , and family burden, especially on the primary caregiver, due to the difficulties in the management of behavioral problems that start from early childhood 13,14,15 . Although scientific evidence has shown the neurobiological basis of the behavioral changes and patterns of hyperphagia, interventions which involve giving guidance to parents and caregivers in respect of parenting practices and the management of the children's behavioral problems are considered to be a priority; previous studies report that these interventions can not only improve a range of behavioral indicators in the children but also help support the caregiver in relation to the emotional difficulties they face [16][17][18][19][20][21] . Parents and/or caregivers in general are the main agents of change in any type of behavioral management of their children 22 .…”
Section: Introductionmentioning
confidence: 99%
“…PWS and ASD exhibit similar levels of ritualistic and repetitive behavior (Greaves et al, 2006;Dimitropoulos & Schultz, 2007). Research on social communication deficits, (i.e., getting along with others, engaging in social reciprocity, and the ability to form friendships) in PWS is limited, but indicates impaired skills compared with other developmental disabilities (Koenig et al, 2004;Rosner et al, 2004) and, in a recent direct comparison to ASD, showed similar difficulties in social responsiveness and competence (Dimitropoulos et al, 2012).…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…For example, although research indicates that individuals with Prader-Willi syndrome (PWS) are at increased risk for ASD, particularly those with the chromosome 15 maternal uniparental disomy genetic subtype (mUPD; Descheemaeker, Govers, Vermeulen, & Fryns, 2006;Dimitropoulos & Schultz, 2007;Greaves, Prince, Evans, & Charman, 2006;Milner et al, 2005), little is known about face processing in PWS. Given that face recognition is widely argued to be related to social impairments in ASD, and research indicates many people with PWS have difficulties with social communication (Cassidy, 1984;Clarke, Boer, Chung, Sturmey, & Webb, 1996;Dimitropoulos, Ho, & Feldman, 2012;Dykens & Cassidy, 1995;Koenig, Klin, & Schultz, 2004;Rosner, Hodapp, Fidler, Sagun, & Dykens, 2004;van Lieshout, de Meyer, Curfs, Koot, & Fryns., 1998), further examination of face processing in PWS is warranted. Furthermore, because maternally inherited duplications of the chromosome 15q11-13 region are found in 1-3% of children with idiopathic autism (Bolton et al, 2001;Cook et al, 1997;Vorstman et al, 2006) and this genotype closely Downloaded by [University of Otago] at 08:36 03 January 2015 resembles PWS mUPD subtype, further characterization of autistic symptomatology may help to explain the role of overexpression of 15q11-13 in these social impairment characteristics.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation